Incomes and labor allocation in community forests in Ciamis Regency - Budiman Achmad; Ris Hadi Purwanto; Sambas Sabarnurdin (Jurnal Ilmu Kehutanan)
Labor for private forest business has not been considered as an important production factor, which it makes the incomes from the private forests is unfavourable. The research was carried out to find out the incomes and labor allocation on private forests management as well as their correlation to farmer characteristics. Data were collected during May to July 2010 at Ciomas, Kalijaya and Kertaharja villages by interviewing sixty purposively selected farmers. Data were analyzed by qualitative and quantitative description. The results revealed that on the basis of land width ownership, the business earned an income to the farmers in Ciomas, Kalijaya and Kertaharja villages of Ciamis district were 6,641,783 IDR/year; 8,029,358 IDR/year, and 6,302,431 IDR/year, respectively. The labors in Kalijaya and Ciomas villages of Ciamis district were mostly allocated to manage private forests i.e. 104.77 MDW/ha/year and 216.93 MDW/ha/year respectively as labors allocation in Kertaharja village were 210.05 MDW/ha/year. The potency of labor absorption level on agriculture sectors in Ciamis district defined as high, which was more than 75 percent. In relation to labor allocation, generally, ages of farmers had positive correlation while the land width had negative ones.